New Perspectives in Southeast Asian and Pacific Prehistory - Piper, Philip J.; Matsumura, Hirofumi; Bulbeck, David (Terra Australis, 2017)
'This volume brings together a diversity of international scholars, unified in the theme of expanding scientific knowledge about humanity's past in the Asia-Pacific region. The contents in total encompass a deep time range, concerning the origins and dispersals of anatomically modern humans, the lifestyles of Pleistocene and early Holocene Palaeolithic hunter-gatherers, the emergence of Neolithic farming communities, and the development of Iron Age societies. These core enduring issues continue to be explored throughout the vast region covered here, accordingly with a richness of results as shown by the authors. Befitting of the grand scope of this volume, the individual contributions articulate perspectives from multiple study areas and lines of evidence. Many of the chapters showcase new primary field data from archaeological sites in Southeast Asia. Equally important, other chapters provide updated regional summaries of research in archaeology, linguistics, and human biology from East Asia through to the Western Pacific.' Mike T. Carson Associate Professor of Archaeology Micronesian Area Research Center University of Guam